PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI RESTORAN CHILI’S GRILL & BAR SARINAH JAKARTA - Andi Rian Segovia; Bambang NS (Human Capital Development, 2017)
Purpose- This study aims to determine the motivation and work environment to have a partial or simultaneous effect on employee performance in Chili’s restaurant Jakarta. Design/methodology/approach- The population in this study were all employees in the Chili's restaurant in Jakarta, with the sample used in this study as many as 100 people. The data analysis method used in this study is the validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and linearity test). While testing hypotheses includes F test, t test, and partial correlation analysis and coefficient of determination (R2). Findings- From the analysis of the correlation (r) and the coefficient of determination (R2) showed a significant effect between motivation and work performance, with a very weak category of 17,6%. The working environment have a significant effect on performance, with a weak category of 22,7%. Motivation and work environment simultaneously significant effect on work performance, with category at 35,7%. The higher motivation and a good working environment, appropiate and adequate hence increasing also the work performance that can be provided by employees on the company.